Adventures in spacetime: circadian rhythms and the dynamics of protein catabolism. Issue 6 (3rd June 2019) - Ryzhikov, Mikhail; Ehlers, Anna; Haspel, Jeffrey A.
ABSTRACT: Circadian rhythms help cells to organize complex processes, but how they shape the kinetics of protein catabolism is unclear. In a recent paper, we employed proteomics to map daily biological rhythms in autophagic flux in mouse liver, and correlated these rhythms with proteasome activity. We also explored the effect of inflammation caused by endotoxin on autophagy dynamics. Our data provide insight into how circadian rhythms serve as a framework for connecting the spatial, temporal, and metabolic aspects of autophagy at a system-wide level. Our observations also have implications for how to optimize autophagy-directed therapies in patients.